Effects observed in the Latin American sector ionospheric F region during the intense geomagnetic disturbances in the early part of November 2004 - Sahai, Y. (2009)
The Sun was very active in the early part of November 2004. During the period of 8-10 November 2004, intense geomagnetic disturbances with two superstorms were observed. In this paper, we have investigated the generation and suppression of equatorial ionospheric irregularities and the daytime changes in the F region electron density in the Latin American sector during the period of intense geomagnetic disturbances. We present the ionospheric sounding observations carried out at Manaus and Sao Jose dos Campos, Brazil, during this geomagnetically disturbed period. Also, GPS observations obtained from several stations in Brazil, Argentina, and St. Croix, U.S. Virgin Islands, during the disturbed period are presented. During the main phase of the first superstorm, around the prereversal enhancement time (night of 7-8 November), prompt penetration of electric field was observed and the presence of equatorial ionospheric irregularities was detected from St. Croix, U.S. Virgin Islands (in the northern hemisphere) to Bahia Blanca, Argentina (in the southern hemisphere). The ionospheric sounding observations at Manaus indicate inhibition of prereversal enhancement on the nights of 9-10 and 10-11 November, possibly due to the disturbed thermospheric winds or disturbance electric fields. Virtually no phase fluctuations on the nights of 9-10 and 10-11 November were observed in the Latin American sector. During the daytime on 8 November, the vertical total electron content (VTEC) observations show a negative storm phase at Porto Alegre (Brazil) and Bahia Blanca (Argentina). Again during the daytime on 10 November, the VTEC observations show a negative storm phase from Brasilia (Brazil) to Bahia Blanca. These negative storm phases are associated with a decrease in the O/N2 ratio. During the daytime on 9 November, the VTEC observations show a positive storm phase extending from St. Croix to Porto Alegre, and again on 10 November, VTEC observations show a positive storm phase. These positive storm phases observed are possibly due to changes in large-scale wind circulation and an increase in the O/N2 ratio.